2018
DOI: 10.1108/edi-08-2017-0156
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing cultural capital: access to employment for women with disabilities in Saudi Arabia

Abstract: Purpose The purpose of this paper is to give voice to the experiences of women with disabilities in the Kingdom of Saudi Arabia (KSA) who have accessed employment, to highlight the structural barriers to employment and to identify the skills they used to obtain work. Design/methodology/approach This is a phenomenological study conducted in KSA. Themes from the interviews of women with disabilities were explored using Yosso’s (2005) cultural capital conceptual framework. Findings The participants had work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Similar results are reported in Western studies which confirms the disadvantages faced by jobseekers with disabilities, particularly women (Hendricks 2010;Seltzer and Krauss 2002;Vogeley et al 2013;Goldberg et al 2003). While shunned in many places in society, IWD are more likely to be supported by close family and friends (Kadi 2018;Peter et al 2018). They receive familial and emotional support from their social circle with mothers having the most influence on their career and employment decisions, followed by fathers and friends (Kadi 2018;Peter et al 2018).…”
Section: Employment Of Individuals With Disabilitiessupporting
confidence: 70%
See 3 more Smart Citations
“…Similar results are reported in Western studies which confirms the disadvantages faced by jobseekers with disabilities, particularly women (Hendricks 2010;Seltzer and Krauss 2002;Vogeley et al 2013;Goldberg et al 2003). While shunned in many places in society, IWD are more likely to be supported by close family and friends (Kadi 2018;Peter et al 2018). They receive familial and emotional support from their social circle with mothers having the most influence on their career and employment decisions, followed by fathers and friends (Kadi 2018;Peter et al 2018).…”
Section: Employment Of Individuals With Disabilitiessupporting
confidence: 70%
“…While shunned in many places in society, IWD are more likely to be supported by close family and friends (Kadi 2018;Peter et al 2018). They receive familial and emotional support from their social circle with mothers having the most influence on their career and employment decisions, followed by fathers and friends (Kadi 2018;Peter et al 2018). However, Abusukkar (2019) reports opposing information; he observed that family members and the broader society in Saudi Arabia did not support the employment of individuals with disabilities, which negatively impacted their career decisions.…”
Section: Employment Of Individuals With Disabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recurring themes emerged while the researchers read and reviewed each publication more closely, guided by the key words and topics that emerged in the bibliometric map. Specifically, the themes identified were: Theme 1 -Career inequalities for women (vs. men) with disabilities (Reed, 2002; see Keim et al, 2002;Heydemann and Johnson, 2019;Ballo, 2020), which falls under the red cluster in Figure 2; Theme 2-Barriers to careers for women with disabilities (see Nosek and Bennett, 1996;Runte, 1998;Reed, 1999;Haq, 2003;Noonan et al, 2004;Conyers et al, 2014;Peter et al, 2018;Hanlon and Taylor, 2022;Scott, 2022), which falls under the green cluster in Figure 2; Theme 3-Educational/curriculum intervention to improve career motivations and opportunities for women with disabilities (see Lindstrom, 2000;Lindstrom and Benz, 2002;Lindstrom et al, 2008Lindstrom et al, , 2012Lindstrom et al, , 2013Lindstrom et al, , 2004Lindstrom et al, , 2019Wehmeyer et al, 2009;Miesch, 2011;Pham et al, 2020;Walden et al, 2021;Hirano et al, 2022), which falls under the green cluster in Figure 2; Theme 4-Facilitators/strategies for careers/career development of women with disabilities (see Nosek and Bennett, 1996;Runte, 1998;Reed, 1999;Keim et al, 2002;Haq, 2003;Noonan et al, 2004;Conyers et al, 2014;Hampton et al, 2015;Valtonen, 2017;…”
Section: Resultsmentioning
confidence: 99%